EFL Students’ Orthographic Competence Using Dictation Task - Siti Marwah Daud; Suleman Bouti; Fahria Malabar (Transbahasa, 2026)
This study investigated EFL students' orthographic competence through a dictation task, focusing on the frequency and distribution of orthographic variations as indicators of grapheme-phoneme correspondence (GPC) mapping competence. A quantitative descriptive design with qualitative interpretation was employed involving 67 fourth-semester students of the English Language Education Study Program at Universitas Negeri Gorontalo selected through purposive sampling. Data were collected using a standardized dictation task consisting of five authentic EFL spoken texts, from which 80 target words representing five orthographic subskills based on Blatt and Prosch's (2014) framework were analyzed: Phonographic-Syllabic (PGS), Morphological (MOR), Peripheral Area (PER), Word Formation (WF), and Syntactic (SYN). Data were analyzed using Arikunto's (2013) percentage formula and qualitative interpretation of recurring error patterns. The analysis identified 1,324 orthographic variations with an overall accuracy rate of 75.30% (Fair). Competence varied across subskills, with SYN showing the lowest performance (28.86%), followed by PGS (59.35%), PER (81.24%), MOR (89.72%), and WF (91.68%). The SYN subskill was mainly characterized by capitalization omissions and literal transcription of spoken punctuation cues, whereas PGS errors reflected cross-linguistic interference from the transparent orthographic system of Indonesian. These findings indicate that EFL orthographic competence is multidimensional and influenced by orthographic memory, cross-linguistic interference, and processing demands. The study recommends regular sentence-level dictation and explicit contrastive orthographic instruction to strengthen orthographic competence.